Analisis Koefisien Serapan (Absorbsi) kebisingan pada Bahan Kayu (Triplek, Papan Kayu dan Kalsiboard) - siti istikhomah; Syahrir Syahrir; Adrianus Inu Natalisanto (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2021)
Noise is a sound that humans do not want and it is an environmental factor that can negatively affect health. To overcome the noise issue, many efforts have been made to reduce noise levels. An example is the manufacture of the walls of a house using materials with sound and absorbent standards. The materials used can also be derived from types of wood such as plywood, wood panels and calciboards. Therefore, the value of its sound absorption coefficient is calculated to find out which active material is to be used in the manufacture of the building. Based on the research results, the value of the sound absorption coefficient of the three types of materials, it can be seen that the shape of the graph and its analysis states that the lowest sound absorption coefficient is most likely at the lower frequencies and the highest value of the sound absorption coefficient tends to be at the higher frequencies. In fact, when viewed as a whole, the magnitude and magnitude of the sound absorption coefficient on the graph is not in line with the increase in the frequency value.